ANALISIS SIFAT KIMIA DAN UJI ORGANOLEPTIK SNACK BAR BERBAHAN DARI CAMPURAN TEPUNG LABU KUNING (Cucurbita moschata) DAN TEPUNG KACANG HIJAU (Vigna radiata) - Singgano, Tania Christy; Koapaha, Teltje; Mamuaja, Christine F. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2019)
Abstract Pumpkin (Cucurbita moschata) is a type of creeper from the Cucurbitaceae family which is orange flesh a sign of carotenoids. Mung beans (Vigna radiata) from the family pabaceae or legumes which have high protein and mineral. Snack bars are a mixture of various ingredients such as cereals, fruits, nuts and then binded by flour. Snacks bar usually foods for people with diabetes and obesity. The study was conducted to have the best nutritional value of snack bars made from pumpkin flour and green bean flour and analyze some physical-chemical qualities. The research method used; Complete Randomized Design (CRD) with 4 treatments and 3 repetitions. The percentage of pumpkin flour and green beans is A (80% pumpkin flour : 20% green bean flour), B (60% pumpkin flour : 40% green bean flour), C (40% pumpkin flour : 60% green bean flour), D (20% pumpkin flour : 80% green bean flour). The results obtained from this study is mixed snack bar formulation 20% pumpkin flour : 80% mung bean flour which had the best nutrients was protein 8,36%, carbohydrate 37,21%, fat 7,10% , ash content 1,45%, moisture content 49,38% with organoleptic test value color 3,88(neutral), aroma 4,36(neutral), texture 4,32(neutral), and flavor 4,08(neutral).Keywords: Pumpkin Flour, Green Bean Flour, Snack Bar